2018
DOI: 10.1136/eb-2017-102848
|View full text |Cite
|
Sign up to set email alerts
|

Clinical imaging in dementia with Lewy bodies

Abstract: Dementia with Lewy bodies (DLB) is a common neurodegenerative dementia in older people; however, the clinical features, particularly cognitive fluctuations and rapid eye movement sleep disorder, are often hard to elicit, leading to difficulty in making the diagnosis clinically. Here we examine the literature for the evidence behind imaging modalities that could assist in making the diagnosis. Dopamine transporter (DAT) imaging remains the best modality for differentiation from dementia of Alzheimer's type with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…Furthermore, as pointed out in a recent review [39], the most significant subcortical changes reported in DLB patients in the literature relate to functional rather than structural imaging data. Finally, the comparison between the AD and DLB groups revealed a relative bilateral preservation of the medial temporal lobe structures in the latter, in line with a number of existing data reviewed by Surendranathan [40].…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, as pointed out in a recent review [39], the most significant subcortical changes reported in DLB patients in the literature relate to functional rather than structural imaging data. Finally, the comparison between the AD and DLB groups revealed a relative bilateral preservation of the medial temporal lobe structures in the latter, in line with a number of existing data reviewed by Surendranathan [40].…”
Section: Discussionsupporting
confidence: 87%
“…DLB is often misdiagnosed and there is need for reliable neuroimaging markers which can distinguish DLB from other types of dementia . DAT scans remain the best neuroimaging technique to differentiate DLB from AD . An abnormal 123 I‐FP‐CIT SPECT strongly supports the diagnosis of DLB, although around 20% of DLB patients (mixed DLB+AD and pure DLB) can have a normal 123 I‐FP‐CIT SPECT .…”
Section: Methodsmentioning
confidence: 99%
“…Occipital hypometabolism on FDG-PET is associated with DLB, 38 and together with relative preservation of posterior cingulate metabolism (the cingulate island sign) e26 is a supportive biomarker of DLB. 2 How frequently the cingulate island sign is seen in prodromal DLB remains to be established; significantly reduced posterior cingulate metabolism may be a useful indication of the concurrence of additional neurofibrillary tangle pathology.…”
Section: Low Occipital Uptake On Perfusion/metabolism Scanmentioning
confidence: 99%